Sequence of the Genome of Salmonella Bacteriophage P22 - Byl, Carolyn Vander (American Society for Microbiology, 2000)
The sequence of the nonredundant region of the Salmonella enterica serovar Typhimurium temperate, serotype-converting bacteriophage P22 has been completed. The genome is 41,724 bp with an overall moles percent GC content of 47.1%. Numerous examples of potential integration host factor and C1-binding sites were identified in the sequence. In addition, five potential rho-independent terminators were discovered. Sixty-five genes were identified and annotated. While many of these had been described previously, we have added several new ones, including the genes involved in serotype conversion and late control. Two of the serotype conversion gene products show considerable sequence relatedness to GtrA and -B from Shigella phages SfII, SfV, and SfX. We have cloned the serotype-converting cassette (gtrABC) and demonstrated that it results in Salmonella serovar Typhimurium LT2 cells which express antigen O1. Many of the putative proteins show sequence relatedness to proteins from a great variety of other phages, supporting the hypothesis that this phage has evolved through the recombinational exchange of genetic information with other viruses.